Problematika Guru Dalam Penerapan Kreatifitas Pada Pelajaran SBDP Kelas 5C di SDN 76 Kota Bengkulu - Lantas Sari; Fitri Kurnia; Illah Fathurrohmi; Rohmizi Putri Ani (Yayasan Darusssalam Bengkulu, 2024)
The independent curriculum is the initial culmination of changes to the 2013 curriculum, where in the independent curriculum children are required to be able to learn independently, think critically and be able to create something, so this is what makes a teacher have to have good basic skills in implementing learning strategies in the independent curriculum. The purpose of this journal is to find out what forms of problems teachers face in applying creativity to SBDP learning and what strategies teachers use to foster creative attitudes in children. The research method in this journal uses a type of qualitative research method which has descriptive or naturalistic principles with natural and industrial conditions. The procedure for collecting data in this journal is by interviewing, observing and observing the ongoing environment. The initial findings in this research were carried out on October 24 2023, where the researchers interviewed directly the Head of Curriculum and the class 5c teacher, Mrs. Head of Curriculum said that before the implementation of the Independent Teachers Curriculum, the capacity to increase IMU had been carried out through workshops and webinars so that the human resources had been equipped. useful knowledge that can be given to students. Next year the independent curriculum must be implemented in all classes such as grades 6 & 3 so that by next year all elementary school students have learned all the material from the independent curriculum that is being implemented.